Parenting Style as a Determinant of AntiSocial Behaviour of Students in Universities in South East, Nigeria - Okwudili Eze, Celestine (International Journal of Psychosocial Rehabilitation, 2021)
The study investigated parenting style as a determinant of antisocial behaviour of students in universities in South East, Nigeria. This study was necessitated by the engagement of university students in some antisocial activities such as breach of school rules and regulations, bad dressing and appearance, destruction of public and school property, fighting and assaults, internet frauds, sexual immorality, examination malpractice, among others. Correlational survey research design was adopted for the study using a sample of 1,250 third year students sampled through multi-stage sampling procedure.Parenting style questionnaire and anti-social behavior questionnaire were used for data collection. Data collected were analyzed using multiple linear regression analysis to answer the research questions and test the null hypotheses. The findings of the study revealed that parenting styles is a significant determinant of students’ antisocial behaviour in both federal and state universities. The findings revealed that parenting style correlated significantly with students’ antisocial behaviour. One of the implications of these findings is that if these antisocial behaviour are not properly checked, they might lead to more social vices like cultism, armed robbery among others. Thus, it was recommended, among others, that parents should be enlightened through seminars and workshops on the appropriate style of parenting to adopt